A Checklist of Angiospermic Flora in and around the Lumbini Sacred Garden, Nepal - Siwakoti, Mohan (Journal of Natural History Museum, 2009)
Lumbini Sacred Garden has stretches of Saccharum dominated grassland and patches of Dalbergia forest. A total of 354 species belonging to 75 families and 245 genera of angiospermic plants has been documented from the Lumbini Sacred Garden and its adjoining areas. Out of these, 258 species belong to 61 families and 187 genera of dicotyledons whereas, 96 species to 14 families and 58 genera of monocotyledons. There are 246 species of herbs, 54 species of trees, 29 species of shrubs and 25 species of Climbers. The paper attempts to give the list of the plants with habit and habitat occurred in Lumbini Sacred Garden and adjoining places. Key words: Angiosperm; flora; Lumbini; Nepal. Journal of Natural History Museum Vol. 23, 2008 Page 27-44